GAMBARAN POLA ASUH ORANG TUA PADA ANAK RETARDASI MENTAL (INTELECTUAL DISABILITY) DI SLB BAKTI SIWI SLEMAN - Dian Rapika Duri; Dwi Yati (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2018)
Background of the Research:The intelectual disability of children is a condition of an abnormal intelligence function that is below average with their own inability appearing before the age of 18 years. Children with mental retardation have low development and intelligence and have difficulties in learning and adapting in the surrounding environment. Parenting patterns of children with intelectual disability is important for their development. Objective: To find out parenting patterns of children with mental retardation (intelectual disability) at SLB BaktiSiwiSleman. Method: This is a non-experimental quantitative research with descriptive approach. The sample of the research was 26 parents selected through total sampling techniques. The instrument was questionnaires. Technique of data analysis using data analysis diskritif with the method of percentage. Finding: The research found the parenting patterns of children with intelectual disability. The data analysis result of 26 respondents revealed that 16 parents (61, 5%) mostly implement authoritative/democratic parenting pattern as the parenting patterns of children with intelectual disability. Meanwhile, there are 2 parents (7, 7%) with permissive parenting patternsand there are 2 other parents implementing authoritarian parenting patterns. Conclusion: The parenting patterns of children with intelectual disability at SLB BaktiSiwiSleman show that there are 16 parents (61, 5%) of 26 parents implement authoritative parenting pattern.